Immunology : mucosal and body surface defences - Williams, Andrew, 1975-; Hussell, Tracy; Lloyd, Clare (Clare M.) (Chichester, West Sussex ; Hoboken, NJ : John Wiley & Sons, 2012)
"The vast majority of medically important pathogens infect their host across a body surface such as the skin, or across a mucosal tissue such as the respiratory tract or intestines, as these sites are the ones exposed to the external environment. By focusing on immunity at mucosal and body surfaces this book presents a fresh, new approach to the teaching of immunology. After an introduction to the basic structure of the immune system, the book looks at two important families of signalling molecules: cytokines and chemokines, before covering the workings of the mucosal immune system. It continues by examining immunity against the four major groups of pathogens - viruses, bacteria, fungi and parasites, and concludes by looking at disorders of the immune system, mucosal tumour immunology and the process of vaccination."--Provided by publisher.
Immunology; Contents; Preface; List of Standard Cells and Symbols; 1 Basic Concepts in Immunology; 1.1 The immune system; 1.2 Tissues and cells of the immune system; 1.3 Activation, regulation and functions of immune responses; 1.4 Innate versus adaptive immunity; 1.5 Primary and secondary immune responses; 1.6 Immune cell development; 1.7 Mast cells and basophils; 1.8 Eosinophils; 1.9 Neutrophils; 1.10 Monocytes and macrophages; 1.11 Dendritic cells; 1.12 Natural killer cells; 1.13 CD4+ T helper cells; 1.14 CD8+ cytotoxic T cells; 1.15 B cells; 1.16 gd T cells; 1.17 Natural killer T cells.
"With contributions from Tracy Hussell, Clare Lloyd."
Includes index.
Print version record.
Keywords: Immunology -- Textbooks; Immune System Phenomena; Mucous Membrane -- immunology; Skin -- immunology; Immunity; MEDICAL -- Immunology; Immunology; Electronic books; Textbooks